2020
DOI: 10.3390/en13040837
|View full text |Cite
|
Sign up to set email alerts
|

Causality Relationship Between Electricity Supply and Economic Growth: Evidence from Pakistan

Abstract: The long-term anticipation of electricity supply (ELS) and demand has supposed substantial prominence in the elementary investigation to offer sustainable resolutions to electricity matters. In this editorial, an outline of the organization of the electricity segment of Pakistan and analysis of historical supply and demand statistics, an up-to-date position of the contrary set of energy plans is presented. The intention of this analysis is to explore the Granger causality relationship between electricity suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…This involved the analysis of the stationarity of the variables and the testing of the cointegration relationship of the variables. The cointegration test indicated the existence of long-term equilibrium relations [65,66,71] consumption between GDP and domestic and non-household consumption electricity. The empirical estimations showed that the estimated coefficients are positive for all regressions, ascertaining the presence of a positive long-term relationship between growth and electricity consumption, in accordance with a number of other studies [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This involved the analysis of the stationarity of the variables and the testing of the cointegration relationship of the variables. The cointegration test indicated the existence of long-term equilibrium relations [65,66,71] consumption between GDP and domestic and non-household consumption electricity. The empirical estimations showed that the estimated coefficients are positive for all regressions, ascertaining the presence of a positive long-term relationship between growth and electricity consumption, in accordance with a number of other studies [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have studied the relationship between GDP and energy consumption [61][62][63][64], providing a number of results in terms of causality, confirming the existence or non-existence of a causality (unilateral or bidirectional) [65][66][67]. Thus, since the 1970s, there has been a strong correlation (almost one to one) between electricity consumption and GDP, but after 1996, this correlation begins to fall apart significantly [68].…”
Section: Gdp and Electric Energy Consumptionmentioning
confidence: 91%
“…The electric transmission effectiveness depends on the capability to decrease losses by decreasing transmitted current, which has been probable by the manufacturing of HV apparatus, e.g., bushings, capacitors and power transformers, etc. The grid of the future must consist of contemporary equipment with innovative design, modern insulating substances and novel expertise to assure safer, consistent, stable and green electricity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of sustainability indicators are available in terms of the environment, economy and society [6]. In recent years, most research on the measurement of environmental impacts and their relationships with social factors has focused on the issue of carbon emissions [7][8][9][10]. As global land use change and greenhouse gas effects are global ecological issues and key research issues in the scope of sustainability [2], there are tons of studies from global [11,12] to Chinese-specific [13,14], and only using carbon emissions to measure the environmental impacts of urbanization would lead to an incomplete picture.…”
Section: Introductionmentioning
confidence: 99%